2010
DOI: 10.26719/2010.16.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections in a neonatal intensive care unit in south-western Saudi Arabia

Abstract: A cohort study measured the occurrence and risk factors of nosocomial infections in the neonatal intensive care unit of Abha general hospital, Saudi Arabia. Of 401 neonates who stayed at least 48 hours in the unit, 77 developed infections, a period prevalence of 19.2% and an incidence of 13.7 infections per 1000 patientdays. The most frequent infections were: pneumonia (50.0%), primary bloodstream (40.9%) and skin and soft tissues (6.5%). In logistic regression analysis, mechanical ventilation (OR = 2.69, 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
3
27
1
Order By: Relevance
“…In this study among nosocomial infections, most infections were pneumonia with a prevalence of 47.7%, which correlate with other studies carried out in other areas of the world that showed the high prevalence of this infection (17)(18)(19)(20)(21)(22)(23)). It appears that one of the reasons that causes this type of infection can be high density of patients in each ward or it is probably due to the use of a ventilator.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study among nosocomial infections, most infections were pneumonia with a prevalence of 47.7%, which correlate with other studies carried out in other areas of the world that showed the high prevalence of this infection (17)(18)(19)(20)(21)(22)(23)). It appears that one of the reasons that causes this type of infection can be high density of patients in each ward or it is probably due to the use of a ventilator.…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence rate of the nosocomial infection is comparable with European countries; the prevalence rates of the nosocomial infection in Norway (13), Italy (14), and France (15) was 5.1%, 5.4%, and 4.9%, respectively. Additionally, in Asian countries, such as the countries of Morocco (6), India (16), Thailand (17), Pakistan (18), and Saudi Arabia (19) is between 5% up to 60%. In some studies that were conducted in Iran, the prevalence rate of nosocomial infection was 4.1%, 0.6%, and 8.4%, respectively in Sari (20), Tehran (7), and Urmia (21), which the prevalence rate of the nosocomial infection was higher than the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study identified 6.6% children with VAP among 451 on mechanical ventilation [25], and a mixed PICU in Australia identified 6.7% children with VAP among 269 on mechanical ventilation [26]. VAP is also common in the NICU and proportions between 6.8% and 57.0% of HAIs have been reported [34,[60][61][62][63][64][65][66]. A Spanish study identified VAP in 9.1% of 198 neonates on mechanical ventilation [67].…”
Section: Epidemiologymentioning
confidence: 99%
“…The vast majority of infections were caused by Gram-positive organisms according to literature -70%, 10%. (14,15) In our study the percentage of these infections has been about 39% in 2010 and was lowered in 2015 to 22.7%. It was accomplished by putting PICCs instead of umbilical venous catheters and peripheral lines.…”
Section: Discussionmentioning
confidence: 91%